Sul dominio della moda e i suoi effetti sulla persona nell'epoca odierna: considerazioni pedagogiche - Tommaso Fratini (Firenze University Press, 2015)
Through a pedagogical lens, this article examines certain characteristics of fashion in an era of the new discontents of civilization. It discusses certain elements of the operation of fashion, especially in relation to the sense of Self and individual identity. The article argues that the current cumbersome place that fashion plays in the lives of individuals has profoundly negative effects on the identity of the contemporary subject. In the last part of the article, a portion is dedicated to the role of education in the face of the relentless pushing of fashion, strongly reaffirming, in accordance with the perspective of critical pedagogy and the model of Self care, a civil position of resistance in the face of the hegemony of prevailing conformism.